2016
DOI: 10.1016/j.bjid.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile outbreak caused by NAP1/BI/027 strain and non-027 strains in a Mexican hospital

Abstract: C. difficile NAP1/BI/027 strain and non-027 strains are established pathogens in our hospital. Accordingly, surveillance of C. difficile infections is now part of our nosocomial prevention program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 44 publications
0
10
1
4
Order By: Relevance
“…14,55 Other less frequent extrinsic RFs were found ( Supplementary Table S1). 65,68 It was observed that in the case-control studies, the most prevalent extrinsic RF was IMV, 40,69,70 followed by previous hospitalization, 35,39 hospitalization time, 71 low McCabe score at admission, 34 gastrostomy or central line-associated bloodstream infection at admission, 34 recent surgery, 34 acute graft rejection, 38 urologic surgery, 35 antacid use, 33 recent exposure to piperacillin-tazobactam, 72 antibiotic use within the last 3 months, 35 prolonged steroid use, 36,39 orotracheal intubation, 70 catheter use ≥7 days, 73 aspiration of secretions, 70 and high Abbreviated Burn Severity Index score. 41 In the SRs, the most commonly mentioned extrinsic RFs were corticosteroid use, [42][43][44] IMV, 42,43,74 blood transfusion, 42,45,74 elective surgery, 43,45 CVC, 43,44 total parenteral nutrition 43,45 and abdominal surgery, 44,45 among others.…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,55 Other less frequent extrinsic RFs were found ( Supplementary Table S1). 65,68 It was observed that in the case-control studies, the most prevalent extrinsic RF was IMV, 40,69,70 followed by previous hospitalization, 35,39 hospitalization time, 71 low McCabe score at admission, 34 gastrostomy or central line-associated bloodstream infection at admission, 34 recent surgery, 34 acute graft rejection, 38 urologic surgery, 35 antacid use, 33 recent exposure to piperacillin-tazobactam, 72 antibiotic use within the last 3 months, 35 prolonged steroid use, 36,39 orotracheal intubation, 70 catheter use ≥7 days, 73 aspiration of secretions, 70 and high Abbreviated Burn Severity Index score. 41 In the SRs, the most commonly mentioned extrinsic RFs were corticosteroid use, [42][43][44] IMV, 42,43,74 blood transfusion, 42,45,74 elective surgery, 43,45 CVC, 43,44 total parenteral nutrition 43,45 and abdominal surgery, 44,45 among others.…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%
“…16,24 In contrast, several studies observed a lower proportion of other intrinsic RFs ( Supplementary Table S1). 31,32 There were fewer intrinsic RFs found in the 12 case-control studies: age, 33 male sex, 34 nervous system diseases, 33 chronic renal failure, 35 acute respiratory distress syndrome, 36 chronic obstructive pulmonary disease, 37,38 previous episode of pneumonia, 39 DM, 37 urinary incontinence, 34 obesity, 34 nonsurgical wounds 40 and local-ized head and neck burns, 41 serum albumin <3.0 g/dL, 39 white blood cells count >12,000/mm 3 . 39 In the 5 included SRs, DM [42][43][44][45] was the most prevalent intrinsic RF, followed by acute renal failure 43,45 and potential renal failure currently on dialysis.…”
Section: Intrinsic Rfs For Infectionmentioning
confidence: 99%
“…It is believed that the apparent severity of the infection caused by the RT027 strain may depend on the comparison with other regional strains and perhaps on differences in the microbiome of the population. In this regard, the results of two studies in the Mexican population are of relevance: one reported a rate of RT027 CDI of 39%, with a CDIattributable mortality of 5%, and the more recent one reported an increase in the rates of CDI in Mexico, with a predominance of more than 50% of RT027 (Davila et al, 2017;Morfin-Otero et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…RCDI may occur due to relapse, defined as the persistence of the same strain causing the initial infection, or reinfection, defined as the acquisition of a genotypically distinct C. difficile strain from an exogenous source [28]. Furthermore, patients with ribotype 027 strains present a higher risk of relapse than those with other ribotypes [7].…”
Section: Relapse and Reinfectionmentioning
confidence: 99%
“…CDI severity has increased in the last decade with outbreaks in the United States, Canada, the United Kingdom, Western Europe, Japan, Korea, China, Hong Kong, and some countries of Latin America. is increased severity has been coincident with the spread of the epidemic strain designated as North American Pulsed (NAP)-field type 01, restriction endonuclease analysis (REA) as group BI, (BI/ RT-027/BI), and polymerase chain reaction (PCR) ribotype (RT) 027 (NAP1/BI/027) [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%